MANFAAT KAWASAN KONSERVASI PESISIR DAN PULAU KECIL (KKP3K) PULAU KOON DAN PERAIRAN SEKITARNYA BAGI PENINGKATAN KEJEHTERAAN MASYARAKAT - Hellen Nanlohy; Natelda R. Timisela; Estradivari Estradivari; Ignatia Dyahapsari; Rizal Rizal (Universitas Pattimura, 2017)
The management of marine resources should be managed effectively and sustainably for the welfare of the people, especially local people living in coastal areas and small islands. This study aims to assess the benefits of marine conservation areas for community welfare. The method used is case study with field survey approach through focus group discussion and then interview with key informant. The research is located in the area of ​​Coastal and Small Islands Conservation (KKP3K3K) Small Island Park-Koon Island, Small Islands and Its Surrounding Waters, East Seram District, Maluku Province. The analytical method used is qualitative descriptive analysis. The results show that coastal communities living around the conservation area know that conservation areas are a prohibition zone for fishing utilization. Determination of this conservation area provides important benefits for coastal communities, especially fishermen because it can increase the catch of fishermen before the establishment of conservation areas.